Cellular characterization based on micropipette aspiration - Goh, Boon Kiat. (2013)
Micropipette aspiration is a technique of using very fine pipettes to apply a suction pressure to a suspended cell and then monitoring the cell deformation into the pipette to study its mechanical characteristics. In this study, porcine Mesenchymal Stem Cells (pMSCs) from a cell line derived from porcine bone marrow were cultured in GlutaMAX culture medium at 5%CO2 and 37oC and allowed to reach at least 80% confluence before micropipette aspiration testing at room temperature of 20oC. Care was taken to ensure cells tested did not exceed passage 9. Viscoelastic behavior and 2 other types of non-viscoelastic behaviors of pMSCs were observed using the hi-speed camera to take snapshots of the aspiration process at specific time intervals and then plotting the aspiration length against time. In a separate experiment, the aspiration length of the cell, LA, at t=300s was recorded, assuming the system to have reached steady state. After which, calculating for stiffness value through a simplified visco-elastic half-space model, it was found that the steady-state Young’s Modulus of pMSCs, E∞, were 471 ± 77 Pa. This appears to be larger than the value of E∞ = 372 ± 125 obtained from human Mesenchymal Stem Cells (hMSCs) obtained in a previous study, (Tan, et al., 2008), and might imply some differences in cytoskeleton structure and density between MSCs of porcine versus human origin. Future studies with larger sample population and more rigorous statistical analysis are recommended to validate this difference.